Assessment of levels and trends of HIV infections among different subgroup populations of Gujarat State - Prioritization of the districts - Suchit Kamble; Padum Narayan; Arvind Panndey; Vinita Verma; Chinmoyee Das (Wolters Kluwer Medknow Publications, 2023)
Background: In India, HIV prevalence varies by region and high-risk groups. General population rates have decreased in high prevalence states through HIV Sentinel Surveillance among pregnant women, while low-moderate prevalence states show variable trends. Gujarat, in western India, has mixed HIV prevalence according to 2017 Sentinel Surveillance data. Objectives: To study the level and trend of HIV positivity among pregnant women and high-risk groups (HRGs) across different districts of the state of Gujarat from year 2012-13 to 2016-17. To review the possible determinants of the HIV epidemic across the selected districts in the state of Gujarat. Materials and Methods: Data from the National AIDS Control Organization (NACO) spanning 2012-17 was analyzed for HIV trends in Gujarat. This included combined HIV testing data from pregnant women at Integrated and Counseling Testing Centers, blood unit testing data from selected districts, and HIV testing among high-risk populations through Targeted Intervention sites. Results: HIV cases in Kheda district declined post-2013-14 among pregnant women (0.38% to 0.21% in 2016-17), and in general ICTC clients (5.53% to 0.264% in 2017-18). MSM seropositivity dropped from 1.15% (2014-15) to 0.74% (2016-17), FSWs from 0.7% (2014-15) to 0.29% (2015-16). Contrastingly, blood donors exhibited an increasing trend, rising from 0.15% (2012-13) to 0.24% (2016-17). In Mehsana, ANC mother seropositivity rose to 0.6% (2013-14), fell to 0.32% (2015-16), and rose again to 0.48% (2016-17). General ICTC clients declined from 1.2% (2012-13) to 0.53% (2016-17). FSWs had 0.25% seropositivity (2015-16), while MSM saw a drop from 0.44% (2014-15) to 0.23% (2016-17). Blood donors' trend was inconsistent. Sabarkantha's pregnant women seropositivity dipped from 0.59% (2012-13) to 0.20% (2014-15), rising to 0.25% (2017-18). General ICTC client seropositivity decreased from 5.34% (2012-13) to 1.17% (2017-18). Conclusion: While declines in HIV prevalence are evident among certain groups such as pregnant women and general ICTC clients, there are fluctuations in seropositivity among high-risk populations like MSM, FSWs, and blood donors. These insights emphasize the need for targeted interventions and ongoing monitoring to effectively address the evolving HIV landscape in these districts.